ANALISIS KESALAHAN BAHASA INGGRIS DALAM MEDIA SOSIAL WHATSAPP - Laloan, Meryen Gladys; Kodong, Fentje; Manus, Jeane A. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTThis research entitled â€œError Analysis of English in Social Media WhatsAppâ€, is an attempt to identify, classify, analyze and describe the kinds of errors in the use of Social Media WhatsApp. This research is expected to help the language development and give information in order to increase knowledge to understand error analysis especially in the WhatsApp. Ellisâ€™s theory is used to identify, classify and analyze the Error Analysis of English in Social Media WhatsApp. This research used an error analysis which has been done in several stages preparation was made by reading text status and chat in the WhatsApp. Data was taken from text status and chat in the WhatsApp. The writer use some techniques of analyzing the data, as follows, identification of error, classification of error and analyze of error. The result of this research shows that there are 71 total data in the â€œtext status